Acute Effects of Different Rest Intervals Between Sets of Resistance Exercise on Neuromuscular Fatigue in Trained Older Women - Jambassi Filho, Jose C. [UNESP]; Gurjao, Andre L. D. [UNESP]; Prado, Alexandre K. G. [UNESP]; Gallo, Luiza H. [UNESP]; Gobbi, Sebastiao [UNESP] (Lippincott Williams & Wilkins, 2020)
Jambassi Filho, JC, Gurjao, ALD, Prado, AKG, Gallo, LH, and Gobbi, S. Acute effects of different rest intervals between sets of resistance exercise on neuromuscular fatigue in trained older women.J Strength Cond Res34(8): 2235-2240, 2020-The aim of this study was to investigate the acute effect of different rest intervals (RIs) between sets on total volume, time under tension, maximal voluntary contraction (MVC), and integrated electromyography (iEMG) activity of the vastus lateralis (VL) and vastus medialis (VM) muscles. Twenty-one resistance-trained older women (66.4 +/- 4.4 years; 69.1 +/- 11.4 kg; 157.5 +/- 5.0 cm) completed 3 different test sessions, performed 48-72 hours apart, in a randomized and counterbalanced within-subjects design. In 2 test sessions, the participants performed 3 sets to voluntary exhaustion with loads that corresponded to 15 maximum repetitions, with either 1-minute RI (RI-1) or 3-minute RI (RI-3). In another test session, the participants remained at rest for 15 minutes. The total volume of exercise and time under tension for the RI-3 session was statistically higher (p <= 0.05) than the RI-1 session. Postexercise MVC for the RI-3 session showed significantly greater reductions (-7.8%;p <= 0.05) compared with the RI-1 and control sessions. No significant changes in postexercise iEMG activity of the VL and VM were shown for any of the sessions (allp> 0.05). The findings of this study suggest that different RIs between sets lead to different acute neuromuscular responses. The longer RI seemed to induce higher neuromuscular fatigue, likely due to higher total volume and time under tension. Thus, longer RI may be a strategy that possibly would lead to greater long-term gains in muscle strength and hypertrophy of the lower limbs in trained older women.
Keywords: aging; electromyography; lower limb; and recovery